Factors Affecting Audit Fee: A Comparison Study of Companies Listed on The Stock Exchange of Thailand, and The Market for Alternative Investment - Phadaeng, Bannasorn; Petchchedchoo, Pattanant; Kumsuprom, Siridech; Panmanee, Panarat (Rajapark Journal, 2024)
This research was to study factors affecting audit fees of listed companies on the Stock Exchange of Thailand (SET) and the Market for Alternative Investment (MAI). Factors related to auditing firms, industrial type, corporate governance mechanism, performance of client’s operation, finance, Thai Financial Reporting Standards (TFRS), and business growth were used to test the effect of audit fees of companies listed in both the SET and the MAI. The samples were collected from the financial statements of each listed company during the period of the year 2018 – the year 2021. Multiple regression and correlation were used to analyze data in the research. The results of the study found that the type of auditing firm of client selection, type of business industry of the client, size of the board of directors, Chief Executive Officer duality, complexity of the client’s company, and some subsidiaries of the client’s company influenced the audit fee of listed companies on both the SET and the MAI. Moreover, independent directors, the size of the client’s company, and the risk of the client’s company affect the audit fees of only companies listed in the SET.